Perancangan Game Engine Untuk Game Visual Novel Berbasis Android Dengan Diagram Alur Cerita - Wu Alvin Hardy; Leo Willyanto; Justinus Andjarwirawan (Jurnal Infra, 2019)
In the process of creating a video game, it takes several core component such as graphic, sound, and animation. Sometimes, in the process of creating those components, some obstacles are encountered due to the number of components are quite large and need to be done manually. Game engine is a software intended to make it easier for developers to create a game. The features in game engine include graphic, sound, and animation, which will help the developer, so the developer do not need to implement those components manually. Visual Novel (VN) is an interactive video game that displays novel stories in the form of static image, audio, and video. A goodVN is made through the narration and dialogue shown between the presented characters, with text along with image and sound which will give an impression of the characters presented as if they live.There is already a variety of game engine for visual novel games, ranging from Android-based Om3ga VNE, desktop-based Ren’Py made with the Python programming language, desktop-based Nscripter, VN Authoring Tool. However, of the many existing game engine for Visual Novel, only Om3ga VNE and VN Authoring Tool can be used on the Android. Even then, the web-based VN Authoring Tool isn’t responsive for mobile device and Om3ga VNE does not provide a feature to make it easier for users to see the outline of the developed video game.In this thesis, an Android-based visual novel game engine is made with the use of Story Flow Diagram (SFD) as the main feature to help user in visual novel creation. Users can see the outline of the storyline with this SFD feature, so that it will make it easier for users to determine the storyline of visual novel that will be created.